A simple nomenclature for a complex proton pump: VHA genes encode the vacuolar H+-ATPase - Sze, Heven; Schumacher, Karin; Müller, Mathias L; Padmanaban, Senthilkumar; Taiz, Lincoln (Trends in plant science, 2002)
The vacuolar-type H+-ATPase acidifies intracellular compartments and is essential for many processes, including cotransport, guard cell movement, development, and tolerance to environmental stress. We have identified at least 26 genes encoding subunits of the vacuolar-type H+-ATPase in the Arabidopsis thaliana genome, although inconsistent nomenclature of these genes is confusing. The pump consists of subunits A through H of the peripheral V1 complex, and subunits a, c, c″ and d of the Vo membrane sector. Most V1 subunits are encoded by a single gene, whereas Vo subunits are encoded by multiple genes found in duplicated segments of the genome. We propose to name these genes VHA-x, where x represents the letter code for each subunit. Applying a consistent nomenclature will help us to understand how the expression, assembly and activity of this pump are integrated with plant growth, signaling, development and adaptation.